Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

When things go wrong: The detrimental interplay of environmental factors on bioturbation in a Jurassic shallow-marine system from western Argentina - Debora M. Campetella; Maximiliano N. Rodriguez; Juan José Ponce; Ainara Irastorza; Martin N. Rogel; Noelia B. Carmona; Nerina Canale; Luis A. Buatois; M. Gabriela Mángano (Journal of South American Earth Sciences, 2026)

Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Use of recombinant gonadotropins in goat MOET programs - Shara D.E. Silva; Lucas M. Figueira; Mariana G.K. Rodriguez; Maria Eduarda A. Teixeira; Bruna W. Freitas; Ribrio Ivan T.P. Batista; Felipe Z. Brandão; Joanna M.G. Souza-Fabjan; Luiz Gustavo B. Siqueira; Jeferson F. Fonseca (Animal Reproduction Science, 2026)

Beyond Coverage: A Systematic Review and Thematic Analysis of Delivery, Compliance, Equity and Impact in Mass Deworming for Soil-Transmitted Helminths - Harley M. Rodriguez; Angelica Marie B. Rostata; Jan Joseph Rainer Christorey Maria Salgado; Timothy Liam D. Rivera; Jose Ma. M. Angeles (Acta Parasitologica, 2026)

Ground level enhancement GLE #77 on 11 November 2025: a data summary - A.L. Mishev; B. Heber; K.-L. Klein; R. Vainio; H. Mavromichalaki; O. Raukunen; N. Larsen; N. Petrov; N. Nikonov; S. Masson; M. Pesce-Rollins; B.T. Kress; et al. (Advances in Space Research, 2026)

Innovative 3D-Image Analysis of Cerebellar Vascularization Highlights Angiogenic Gene Dysregulations in a Murine Model of Apnea of Prematurity - A. Rodriguez-Duboc; C. Racine; M. Basille-Dugay; D. Vaudry; B. Gonzalez; D. Burel (The Cerebellum, 2026)
Apnea of prematurity (AOP) affects 50% of preterm infants causing intermittent hypoxia (IH), which can lead to long-term neurodevelopmental deficits. Cerebellar abnormalities have been observed in AOP but the relationship between vascular alterations and neural development remains unclear. This study investigates how IH affects cerebellar angiogenesis using a murine model of AOP. We developed an innovative 3D imaging workflow combining Imaris and VesselVio software to quantitatively analyze cerebellar vascularization at different postnatal stages (P4, P8, P12, P21, and P70). We correlated these results with a transcriptomic analysis of 23 angiogenesis-related genes in the same stages to uncover the associated molecular pathways. We found that IH induced significant vascular changes, particularly at P4, with a global increase in vascular-network dimensions. By P8, the vascular network normalized, but genes were downregulated in all pathways studied. After P12, at the end of the IH protocol, transcriptional regulations had varied but persisted long-term. Moreover, differential analysis showed distinct effects on superficial versus deep vascular networks, allowing for a more precise understanding of remodeling patterns throughout development. Overall, transcriptomic changes were associated with morphological alterations in a time-dependent manner, suggesting a multiphasic IH response through development with lasting effects. Key regulations included VEGF, angiopoietin, and matrix metalloprotease signaling. These findings demonstrate that IH disrupts cerebellar angiogenesis in parallel with neurogenesis, potentially contributing to the neurodevelopmental deficits observed in AOP. Thus, the interconnected nature of angio- and neurogenesis during cerebellar development makes it crucial to take vascular aspects into account in therapeutic approaches to neurodevelopmental disorders.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Decoupled Climatic Drivers of Tree and Ground‐Layer Carbon Uptake in Mountain Ecosystems Around the World - Max Mallen‐Cooper; Maja K. Sundqvist; David A. Wardle; Radim Šarlej; Rose E. Brinkhoff; Aimée T. Classen; Eliška Kuťáková; Daniel B. Metcalfe; M. Noelia Barrios‐Garcia; Julie R. Deslippe; Kobayashi Makoto; Jane Mallen‐Cooper; et al. (Global Change Biology, 2026)
One of the key ecological processes affected by climate change is plant carbon uptake. However, there is substantial uncertainty about how plant carbon uptake will respond to warming in mountain ecosystems, which are known for sharp temperature gradients and abrupt shifts in vegetation structure. Specifically, we lack an understanding of whether these response trajectories over time will be linear or non‐linear, and how they might vary among mountain ecosystems globally. Here, we measured ecosystem Gross Primary Productivity (GPP) along forest‐tundra elevational gradients in the mountain regions of five countries (Argentina, Australia, France, Sweden, USA) to infer future trajectories of carbon uptake, and whether any non‐linear changes might occur. We also examined the role of microclimate in driving GPP responses. We found that whole‐ecosystem GPP increased with increasing macroclimatic temperature (decreasing elevation), but this response was dominated by a sharp non‐linear increase at the transition from tundra to forest (i.e., the treeline). In contrast, ground‐layer GPP was largely independent of macroclimate, but often responded strongly, and linearly, to microclimate (growing degree days > 5°C, mean growing season temperature). This pattern reflected a frequent decoupling of microclimate from the expected temperature‐elevation relationship, likely driven by such processes as cold‐air drainage, limited near‐surface air mixing, and shading by trees. The contrasting responses of GPP among global temperature gradients indicates strong context dependence at both local and continental scales, although in a few cases, biomass and leaf nitrogen were important moderators. These findings suggest that future shifts in carbon uptake in mountains will be mainly controlled by tree range expansion. Our results highlight the need to consider species responses on different spatial scales, and to increase representation of undersampled regions to capture the full breadth of ecological responses to climate change.

Rethinking nature-based solutions in informal settlements: community perceptions of urban risk in Durán, Ecuador - Margot Mattson; Isabella Pacenza; Shruti Jadala; Carlos Romero; Addison Martin; Marta Berbes-Blazquez; Elizabeth M. Cook; Mathieu Feagan; Mercy Borbor-Cordova; Pilar Cornejo-Rodriguez; Nancy B. Grimm (Climate and Development, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Natal homing in male green turtles (Chelonia mydas) from two neotropical islands - Marco A. Garcia-Cruz; Kathryn M. Rodriguez-Clark; Karen A. Bjorndal; Alan B. Bolten; Eugenia Naro-Maciel; Claudio Bellini; Brian Shamblin; Carlos Carreras (Frontiers in Marine Science, 2026)
Studying the origins of male green turtles is critical for assessing their poorly understood natal homing behavior, compared to that of females, which have a high degree of fidelity to their nesting beach of their birth. Between 2005 and 2012, we collected 379 tissue samples from male and female green turtles ( Chelonia mydas ) to test the hypothesis that there is no difference in natal homing between the sexes in two tropical Island mating areas of the western Atlantic: Isla de Aves, Venezuela, and Atol das Rocas, Brazil. We sequenced an ~800bp fragment of the mtDNA control region from each individual and characterized their haplotype profiles. Comparisons between males and females from rookeries and their closely associated offshore courtship areas revealed no significant genetic differentiation between males and females at either site, suggesting that males also return to their hatching site to breed. To examine fidelity of males to their natal region in more depth, we combined our results with published data from 2,350 individuals from 31 green turtle rookeries in the Gulf of Mexico, Caribbean Sea, Atlantic Ocean, and the Mediterranean Sea. Considering contributions of 1% or more, a mixed stock analysis of four regional haplotype groups revealed that adult males sampled at Isla de Aves originated from rookeries in the eastern Caribbean, mainly from Isla de Aves itself (95.3%). Also, haplotype frequencies indicated that adult males sampled at Atol das Rocas originated mainly from Atol das Rocas (74.5%), possibly with small (on average 4%) contributions from five other regional rookeries. These combined results also suggest that males from both Isla de Aves and Atol das Rocas return to their natal regions to reproduce, as do females. This study provides the first direct evidence of male natal homing in green turtles in two populations of the western Atlantic and confirms that this phenomenon, previously observed in Australian green turtles, also occurs there. Understanding the factors that contribute to varying degrees of homing to courtship areas is essential for evaluating the demographic independence of populations. It further allows for a more accurate assessment of their vulnerability to regional threats.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Developing a cost and time efficient strategy for assessing novel materials for wastewater treatment with non-target screening analysis - Alba Rodriguez-Otero; Selina Tisler; Lisa M. Reinhardt; Mathias B. Jørgensen; David I. Pattison; Brice Bouyssiere; Jan H. Christensen (Journal of Hazardous Materials, 2026)

Integrative systematics of the Brazilian tree “sucupira”: morphological, cytogenetic and genomic boundaries of Pterodon emarginatus Vogel and P. pubescens (Benth.) Benth. (Leguminosae, Papilionoideae) - Victória B. Albernaz; Yennifer Mata-Sucre; Mariela A. Sader; Pablo E. Rodriguez; Cíntia P. Targueta; Adriana M. Antunes; Rafael B. Pinto; André Marques; Dulce Maria Sucena D. A. Rocha; Gustavo Souza; Thannya N. Soares (Systematics and Biodiversity, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Intact glycoconjugates from Taenia crassiceps excreted/secreted products ameliorate chemically induced colitis by modulating inflammation and strengthening adherens junctions - Yadira Ledesma-Soto; Ilse Chávez-Soto; Marissa Calderón-Torres; Andrea Monserrat Rodríguez-Lozoya; Jonadab E. Olguin; Luis B. Hernández-Portilla; César M. Flores-Ortíz; Fernando Candanedo; Miriam Rodriguez-Sosa; Sonia E. Hernández-Navia; Luis I. Terrazas (Inflammopharmacology, 2025)
Background Ulcerative colitis (UC) is a chronic inflammatory disease that is increasing in prevalence worldwide. Notably, helminth infections, known for their immunoregulatory properties, are inversely related to inflammatory conditions such as UC. Research has indicated that Taenia crassiceps infection can improve inflammatory-mediated diseases, including type 1 diabetes, experimental autoimmune encephalomyelitis, and colitis. Subsequent studies revealed that helminth-derived products can replicate the effects of complete infection in the context of inflammatory diseases; however, the mechanisms underlying these effects remain unclear. This study examined the impact of intact glycans from T. crassiceps excreted/secreted products (TcES) on host responses to dextran sodium sulfate (DSS)-induced colitis. Methods UC was induced by administering 4% DSS in the drinking water for 9 days. The mice were treated with intact TcES, glycan-depleted TcES, or protein-depleted TcES 2 days after colitis induction. Symptoms of the disease, along with immunologic and histopathological evaluations, were performed. Results Colitic mice that received intact TcES presented fewer disease symptoms and less histopathological damage. Intact TcES reduced the proinflammatory response while increasing the production of IL-4, IL-22, IL-31, and MCP-1 and promoting M2 macrophage polarization via PD-L2 expression. Furthermore, intact TcES diminished neutrophil infiltration, inhibited NF-κB and p38 phosphorylation in the colon, and suppressed reactive oxygen species and 3-nitrotyrosine levels, thus protecting the colon. These effects were accompanied by increased expression of E-cadherin and β-catenin, indicating improved epithelial barrier integrity. Conversely, mice treated with glycan-depleted or protein-depleted TcES exhibited exacerbated colitis characterized by disruption of colon tissue architecture, extensive inflammation, and epithelial damage, including loss of E-cadherin and β-catenin and a lack of M2 macrophage polarization. Conclusions Glycoconjugates on TcES play a significant role in mediating the immunomodulatory effects that alleviate DSS-induced colitis.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Nutritional ketosis modulates the methylation of cancer-related genes in patients with obesity and in breast cancer cells - Paula M Lorenzo; Andrea G Izquierdo; Gemma Rodriguez-Carnero; Nicolas Costa-Fraga; Angel Díaz-Lagares; Cristina Porca; Daniel de Luis; Cristina Tejera; Laura De Paz; Juan Cueva; Diego Bellido; Ana B Crujeiras (Journal of Physiology and Biochemistry, 2025)
Scientific evidence demonstrates that a very low-calorie ketogenic diet (VLCKD) is effective and beneficial in the treatment of obesity, capable of reversing the methylome associated with obesity and has immunomodulatory capacity. This effect is in part promoted by nutritional ketosis and could be involved in counteracting obesity-related cancer. The aim of this study was to evaluate the effect of nutritional ketosis on the methylation of genes related to tumor processes in patients with obesity and in breast cancer cells. Based on methylome data (Infinium MethylationEPIC BeadChip, Illumina) from patients with obesity treated with a VLCKD for weight loss ( n = 10; n = 5 women, age = 48.8 ± 9.20 years, BMI = 32.9 ± 1.4 kg/m2), genes belonging to cancer-related pathways were specifically evaluated and further validated in vitro in MDA-MB-231 (triple negative) and MCF7 (RE positive) breast tumor cells pretreated for 72 h with βOHB, the main ketone body, secretome from visceral (VATs) or subcutaneous (SATs) adipose tissue of patients with obesity. The cell tumoral phenotype was evaluated by proliferation assay and expression of cancer-related genes. VLCKD-induced nutritional ketosis promoted changes in the methylation of 18 genes (20 CpGs; 17 hypomethylated, 3 hypermethylated) belonged to cancer-related pathways with MAPK10, CCN1, CTNNA2, LAMC3 and GLI2 being the most representative genes. A similar pattern was observed in the MDA-MB-231 cells treated with β-OHB, without changes in MCF7. These epigenetic changes paralleled the tumoral phenotype modulated by the treatments. Taking together these results highlight the potential role of VLCKD as an adjuvant to anticancer treatment in groups more susceptible to the development of cancer such as patients with obesity, exerting epigenetic regulation through nutritional ketosis and weight loss.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Charge as a key physicochemical factor in adsorption of organic micropollutants from wastewater effluent by rice husk bio-silica - Alba Rodriguez-Otero; Selina Tisler; Lisa M. Reinhardt; Mathias B. Jørgensen; Brice Bouyssiere; Jan H. Christensen (Water Research, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Screening mammography frequency following dense breast notification among a predominantly Hispanic/Latina screening cohort - Erica J. Lee Argov; Carmen B. Rodriguez; Mariangela Agovino; Karen M. Schmitt; Elise Desperito; Anita G. Karr; Ying Wei; Mary Beth Terry; Parisa Tehranifar (Cancer Causes & Control, 2024)

Sunflower yield gaps and their causes in Argentina - Ignacio M. Rodriguez; Antonio J. Hall; Juan P. Monzon; Jorge L. Mercau; Sofia Gayo; Monica Lopez Pereira; Anibal Cerrudo; Hernán A. Urcola; Carolina B. Troglia; Sebastián Zuil; María Paolini; Gustavo Martini; et al. (Field Crops Research, 2024)

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Quis custodiet ipsos custodes? A call for community participation in the governance of the SeqCode - Iain C. Sutcliffe; Luis M. Rodriguez-R; Stephanus N. Venter; William B. Whitman (Systematic and Applied Microbiology, 2024)

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Considerations for the development of guidance on dose level selection for developmental and reproductive toxicity studies - R.W. Lewis; A.K. Andrus; J. Arroyo; S. Brescia; P.A. Botham; M. Corvaro; G.P. Daston; T. Hofmann; C. Rodriguez; F. Sewell; B. van Ravenzwaay; K. Wiench; et al. (Regulatory Toxicology and Pharmacology, 2024)

Analysis of an optical imaging system prototype for autonomously monitoring zooplankton in an aquaculture facility - M.N. Bowman; R.A. McManamay; A. Rodriguez Perez; G. Hamerly; W. Arnold; E. Steimle; K. Kramer; B. Norris; D. Prangnell; M. Matthews (Aquacultural Engineering, 2024)

Current deformation along the northern Caribbean plate boundary from GNSS measurements in Cuba - E. Calais; O.F. Gonzalez; E.D. Arango-Arias; B. Moreno; R. Palau; M. Cutie; E. Diez; C. Montenegro; E. Rodriguez Roche; J. Garcia; E. Castellanos; S. Symithe (Tectonophysics, 2023)

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Improving the design and conduct of aquatic toxicity studies with oils based on 20 years of CROSERF experience - WA Stubblefield; M Barron; G Bragin; ME DeLorenzo; B de Jourdan; B Echols; DP French-McCay; P Jackman; JR Loughery; TF Parkerton; DA Renegar; JL Rodriguez-Gil (Aquatic Toxicology, 2023)

Evaluation of reference genes for qRT-PCR studies in the colchicine producing Gloriosa superba L. - Nekha Johnson; Diana Rodriguez Diaz; Sivakumar Ganapathy; John S. Bass; Toni M. Kutchan; Abdul L. Khan; Albert B. Flavier (Plant Biotechnology Reports, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

PFAS levels and exposure determinants in sensitive population groups - L. Fábelová; A. Beneito; M. Casas; A. Colles; L. Dalsager; E. Den Hond; C. Dereumeaux; K. Ferguson; L. Gilles; E. Govarts; A. Irizar; M.J. Lopez Espinosa; et al. (Chemosphere, 2023)

The Challenges of Characterizing the Zooplankton Community Response Following Simulated Spills of Diluted Bitumen into Boreal Lake Limnocorrals - T. A. Black; M. J. Paterson; L. Timlick; J. Cederwall; J. M. Blais; B. Hollebone; D. M. Orihel; V. P. Palace; J. L. Rodriguez-Gil; M. L. Hanson (Bulletin of Environmental Contamination and Toxicology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Validity of a portable X-ray fluorescence device for analyzing field dust wipe samples for lead - A. B. Obeng; M. Del Rio; C. Costa; C. Chavarria; C. Rodriguez; M. B. Galkaduwa; C. Wekumbura; K. Gamage; G. M. Hettiarachchi; W. Hargrove; C. Sobin (International Journal of Environmental Science and Technology, 2022)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Increasing Vascular Response to Injury Improves Tendon Early Healing Outcome in Aged Rats - Corinne N. Riggin; Stephanie N. Weiss; Ashley B. Rodriguez; Harina Raja; Mengcun Chen; Susan M. Schultz; Chandra M. Sehgal; Louis J. Soslowsky (Annals of Biomedical Engineering, 2022)

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Spontaneously fermented traditional beverages as a source of bioactive compounds: an overview - R. B. Cuvas-Limon; Clarisse Nobre; Mario Cruz; Rosa M. Rodriguez-Jasso; Héctor A. Ruíz; Araceli Loredo-Treviño; J. A. Texeira; Ruth Belmares (Critical Reviews in Food Science and Nutrition, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

An intrapopulational study of organic compounds and biomechanical properties of the shell of the Antarctic bivalve Laternula elliptica (P. P. King, 1832) at King George Island - M. Roberto García-Huidobro; María Josefina Poupin; Cristóbal Urrutia; Alejandro B. Rodriguez-Navarro; Christian Grenier; Juan F. Vivanco; Laura Ramajo; Isabel Benjumeda; Nelson A. Lagos; Marco A. Lardies (Polar Biology, 2021)

Cyclodextrins: a tool in plant cell and organ culture bioprocesses for the production of secondary metabolites - A. B. Cardillo; M. Perassolo; A. M. Giulietti; Julian Rodriguez Talou (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Managing groundwater supplies subject to drought: perspectives on current status and future priorities from England (UK) - M. J. Ascott; J. P. Bloomfield; I. Karapanos; C. R. Jackson; R. S. Ward; A. B. McBride; B. Dobson; N. Kieboom; I. P. Holman; A. F. Van Loon; E. J. Crane; B. Brauns; et al. (Hydrogeology Journal, 2021)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Dynamics of volatilomes emitted during cross-talking of plant-growth-promoting bacteria and the phytopathogen, Fusarium solani - A. Gutiérrez-Santa Ana; H. A. Carrillo-Cerda; J. Rodriguez-Campos; J. B. Velázquez-Fernández; O. A. Patrón-Soberano; S. M. Contreras-Ramos (World Journal of Microbiology and Biotechnology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Three-dimensional regional bi-ventricular shape remodeling is associated with exercise capacity in endurance athletes - G. Bernardino; M. Sanz de la Garza; B. Domenech-Ximenos; S. Prat-Gonzàlez; R. J. Perea; I. Blanco; F. Burgos; A. Sepulveda-Martinez; M. Rodriguez-Lopez; F. Crispi; C. Butakoff; M. A. González Ballester; et al. (European Journal of Applied Physiology, 2020)

Dense Mytilus Beds Along Freshwater-Influenced Greenland Shores: Resistance to Corrosive Waters Under High Food Supply - Carlos M. Duarte; Alejandro B. Rodriguez-Navarro; Antonio Delgado-Huertas; Dorte Krause-Jensen (Estuaries and Coasts, 2020)

SPEXOR passive spinal exoskeleton decreases metabolic cost during symmetric repetitive lifting - S. J. Baltrusch; J. H. van Dieën; A. S. Koopman; M. B. Näf; C. Rodriguez-Guerrero; J. Babič; H. Houdijk (European Journal of Applied Physiology, 2020)

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Satellite Remote Sensing for Coastal Management: A Review of Successful Applications - Matthew J. McCarthy; Kaitlyn E. Colna; Mahmoud M. El-Mezayen; Abdiel E. Laureano-Rosario; Pablo Méndez-Lázaro; Daniel B. Otis; Gerardo Toro-Farmer; Maria Vega-Rodriguez; Frank E. Muller-Karger (Environmental Management, 2017)

Engaging diverse populations in biospecimen donation: results from the Hoy y Mañana study - Elisa M. Rodriguez; Frances G. Saad-Harfouche; Austin Miller; Martin C. Mahoney; Christine B. Ambrosone; Carl D. Morrison; Willie Underwood; Deborah O. Erwin (Journal of Community Genetics, 2016)

Biomineralization changes with food supply confer juvenile scallops ( Argopecten purpuratus ) resistance to ocean acidification - Laura Ramajo; Núria Marbà; Luis Prado; Sophie Peron; Marco A. Lardies; Alejandro B. Rodriguez‐Navarro; Cristian A. Vargas; Nelson A. Lagos; Carlos M. Duarte (Global Change Biology, 2016)
Future ocean acidification ( OA ) will affect physiological traits of marine species, with calcifying species being particularly vulnerable. As OA entails high energy demands, particularly during the rapid juvenile growth phase, food supply may play a key role in the response of marine organisms to OA . We experimentally evaluated the role of food supply in modulating physiological responses and biomineralization processes in juveniles of the Chilean scallop, Argopecten purpuratus, that were exposed to control ( pH ~ 8.0) and low pH ( pH ~ 7.6) conditions using three food supply treatments (high, intermediate, and low). We found that pH and food levels had additive effects on the physiological response of the juvenile scallops. Metabolic rates, shell growth, net calcification, and ingestion rates increased significantly at low pH conditions, independent of food. These physiological responses increased significantly in organisms exposed to intermediate and high levels of food supply. Hence, food supply seems to play a major role modulating organismal response by providing the energetic means to bolster the physiological response of OA stress. On the contrary, the relative expression of chitin synthase, a functional molecule for biomineralization, increased significantly in scallops exposed to low food supply and low pH , which resulted in a thicker periostracum enriched with chitin polysaccharides. Under reduced food and low pH conditions, the adaptive organismal response was to trade‐off growth for the expression of biomineralization molecules and altering of the organic composition of shell periostracum, suggesting that the future performance of these calcifiers will depend on the trajectories of both OA and food supply. Thus, incorporating a suite of traits and multiple stressors in future studies of the adaptive organismal response may provide key insights on OA impacts on marine calcifiers.

First recurrence of Clostridium difficile infection: clinical relevance, risk factors, and prognosis - T. Larrainzar-Coghen; D. Rodriguez-Pardo; M. Puig-Asensio; V. Rodríguez; C. Ferrer; R. Bartolomé; C. Pigrau; N. Fernández-Hidalgo; T. Pumarola; B. Almirante (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Toxicity assessment through multiple endpoint bioassays in soils posing environmental risk according to regulatory screening values - A. Rodriguez-Ruiz; V. Asensio; B. Zaldibar; M. Soto; I. Marigómez (Environmental Science and Pollution Research, 2014)

High-quality conforming hexahedral meshes of patient-specific abdominal aortic aneurysms including their intraluminal thrombi - J. Tarjuelo-Gutierrez; B. Rodriguez-Vila; D. M. Pierce; T. E. Fastl; P. Verbrugghe; I. Fourneau; G. Maleux; P. Herijgers; G. A. Holzapfel; E. J. Gomez (Medical & Biological Engineering & Computing, 2014)

Genetic variation within a dominant shrub structures green and brown community assemblages - Gregory M. Crutsinger; Mariano A. Rodriguez-Cabal; Adam B. Roddy; Kabir G. Peay; Justin L. Bastow; Allison G. Kidder; Todd E. Dawson; Paul V. A. Fine; Jennifer A. Rudgers (Ecology, 2014)
Two rising challenges in ecology are understanding the linkages between above‐ and belowground components of terrestrial ecosystems and connecting genes to their ecological consequences. Here, we blend these emerging perspectives using a long‐term common‐garden experiment in a coastal dune ecosystem, whose dominant shrub species, Baccharis pilularis , exists as erect or prostrate architectural morphotypes. We explored variation in green (foliage‐based) and brown (detritus‐based) community assemblages, local ecosystem processes, and understory microclimate between the two morphs. Prostrate morphs supported more individuals, species, and different compositions of foliage arthropods, litter microarthropods, and soil bacteria than erect morphs. The magnitude of community compositional differences was maintained from crown to litter to soil. Despite showing strikingly similar responses, green and brown assemblages were associated with different underlying mechanisms. Differences in estimated shrub biomass best explained variation in the green assemblage, while understory abiotic conditions accounted for variation in the brown assemblage. Prostrate morphs produced more biomass and litter, which corresponded with their strong lateral growth in a windy environment. Compared to erect morphs, the denser canopy and thicker litter layer of prostrate morphs helped create more humid understory conditions. As a result, decomposition rates were higher under prostrate shrubs, despite prostrate litter being of poorer quality. Together, our results support the hypothesis that intraspecific genetic variation in primary producers is a key mediator of above‐ and belowground linkages, and that integrating the two perspectives can lead to new insights into how terrestrial communities are linked with ecosystem pools and processes.

The Immune System in Stroke: Clinical Challenges and Their Translation to Experimental Research - Craig J. Smith; Catherine B. Lawrence; Beatriz Rodriguez-Grande; Krisztina J. Kovacs; Jesus M. Pradillo; Adam Denes (Journal of Neuroimmune Pharmacology, 2013)

Relationship between hydraulic conductance and citrus dwarfing by the Flying Dragon rootstock (Poncirus trifoliata L. Raft var. monstruosa) - B. Martínez-Alcántara; J. Rodriguez-Gamir; M. R. Martínez-Cuenca; D. J. Iglesias; E. Primo-Millo; M. A. Forner-Giner (Trees, 2013)

Cr(VI) Adsorption and Desorption on Soils and Biosorbents - M. T. Fernández-Pazos; B. Garrido-Rodriguez; J. C. Nóvoa-Muñoz; M. Arias-Estévez; M. J. Fernández-Sanjurjo; A. Núñez-Delgado; E. Álvarez (Water, Air, & Soil Pollution, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Prevention of group B streptococcal neonatal disease revisited. The DEVANI European project - J. Rodriguez-Granger; J. C. Alvargonzalez; A. Berardi; R. Berner; M. Kunze; M. Hufnagel; P. Melin; A. Decheva; G. Orefici; C. Poyart; J. Telford; A. Efstratiou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Aberrant epigenetic regulation of bromodomain Brd4 in human colon cancer - R. M. Rodriguez; C. Huidobro; R. G. Urdinguio; C. Mangas; B. Soldevilla; G. Domínguez; F. Bonilla; A. F. Fernandez; M. F. Fraga (Journal of Molecular Medicine, 2012)

On the effects of the ionospheric disturbances on precise point positioning at equatorial latitudes - B. Moreno; S. Radicella; M. C. de Lacy; M. Herraiz; G. Rodriguez-Caderot (GPS Solutions, 2011)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Dendritic vulnerability in neurodegenerative disease: insights from analyses of cortical pyramidal neurons in transgenic mouse models - Jennifer I. Luebke; Christina M. Weaver; Anne B. Rocher; Alfredo Rodriguez; Johanna L. Crimins; Dara L. Dickstein; Susan L. Wearne; Patrick R. Hof (Brain Structure and Function, 2010)

Shallow lake trophic status linked to late Holocene climate and human impacts - Matthew N. Waters; Michael F. Piehler; Antonio B. Rodriguez; Joseph M. Smoak; Thomas S. Bianchi (Journal of Paleolimnology, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

The Mitochondrial ATP-Sensitive Potassium Channel Blocker 5-Hydroxydecanoate Inhibits Toxicity of 6-Hydroxydopamine on Dopaminergic Neurons - J. Rodriguez-Pallares; J. A. Parga; B. Joglar; M. J. Guerra; J. L. Labandeira-Garcia (Neurotoxicity Research, 2009)

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Toxicity of Santander Bay Sediments to the Euryhaline Freshwater Oligochaete Limnodrilus hoffmeisteri - P. Rodriguez; J. Arrate; M. Martinez-Madrid; T. B. Reynoldson; V. Schumacher; J. Viguri (Hydrobiologia, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Melatonin increases the survival time of animals with untreated mammary tumours: Neuroendocrine stabilization - M. C. Saez; C. Barriga; J. J. Garcia; A. B. Rodriguez; J. Masot; E. Duran; E. Ortega (Molecular and Cellular Biochemistry, 2005)

Cellular cardiomyoplasty: development of a technique to culture human myoblasts for clinical transplantation - M. Esther Rendal Vázquez; M. Rodriguez Cabarcos; T. Diaz Román; A. Juffé Stein; N. Doménech Garcia; B. Adrio Nazar; M.J. Sánchez Dopico; C. Andión Núñez; F.J. Blanco Garcia (Cell and Tissue Banking, 2005)

Clinical characteristics and significance of Streptococcus salivarius bacteremia and Streptococcus bovis bacteremia: a prospective 16-year study - J. C. Corredoira; M. P. Alonso; J. F. García; E. Casariego; A. Coira; A. Rodriguez; J. Pita; C. Louzao; B. Pombo; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Environmental Education as a Component of Multidisciplinary Conservation Programs: Lessons from Conservation Initiatives for Critically Endangered Fruit Bats in the Western Indian Ocean - W. J. TREWHELLA; K. M. RODRIGUEZ‐CLARK; N. CORP; A. ENTWISTLE; S. R. T. GARRETT; E. GRANEK; K. L. LENGEL; M. J. RABOUDE; P. F. REASON; B. J. SEWALL (Conservation Biology, 2005)
Pteropus livingstonii , P. voeltzkowi , and P. rodricensis are three critically endangered fruit bats from western Indian Ocean islands for which multidisciplinary conservation programs have been established that include environmental education programs (EEPs). We describe these EEPs in terms of the strategies used to achieve them and evaluate the educational and conservation outcomes and impacts of the programs. Educational outputs (including posters, stickers, videos, lesson plans, and workshops), primarily linking human needs to the ecosystem services provided by bats, were delivered to schools and community groups, and local environmental educators were trained to further develop the EEPs. Outcomes included increased local awareness about the bats and their conservation, training of environmental educators, inclusion of bat conservation and environmental issues in the school curricula, and establishment of community‐based environmental nongovernmental organizations (NGOs). Extensive prior planning, presentations in local languages, distribution of outputs through existing networks of educators, training of local educators, establishment of local environmental NGOs, and local capacity‐building were all associated with these EEPs achieving their goals in the under‐resourced island locations where these bats are found. The EEPs were also important in the development of other components of their respective conservation programs, such as population monitoring programs. Although long‐term conservation impacts, particularly tackling habitat loss, are slow to materialize and social and economic issues need to be addressed, these EEPs have already had important outcomes and have established the foundation for future conservation actions.

Experimental Study of the Formation of Chlorination By-Products in Potable Water of Quebec City, Canada - M. J. Rodriguez; M. Huard; J.-B. Srodes (Bulletin of Environmental Contamination and Toxicology, 2004)

Somatic embryogenesis in Citrus SPP.: Carbohydrate stimulation and histodifferentiation - Márcio L. Tomaz; Beatriz M. Januzzi Mendes; francisco De Assis A. Mourão Filho; Clarice G. B. Demétrio; Naratip Jansakul; Adriana P. Martinelli Rodriguez (In Vitro Cellular & Developmental Biology - Plant, 2001)

A novel approach for the definition of the inorganic medium components for micropropagation of yellow passionfruit (Passiflora edulis sims. F. Flavicarpa Deg.) - A. C. B. de A. Monteiro; E. N. Higashi; A. N. Gonçalves; A. P. M. Rodriguez (In Vitro Cellular & Developmental Biology - Plant, 2000)

Linkage mapping and QTL analysis in coconut (Cocos nucifera L.) - A. Herrán; L. Estioko; D. Becker; M. J. B. Rodriguez; W. Rohde; E. Ritter (Theoretical and Applied Genetics, 2000)

A statistical approach to study the dynamics of micropropagation rates, using banana ( Musa spp.) as an example - B. M. J. Mendes; S. B. Filippi; C. G. B. Demétrio; A. P. M. Rodriguez (Plant Cell Reports, 1999)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Phylogeography of the West Indian manatee ( Trichechus manatus ): how many populations and how many taxa? - A. I. GARCIA‐RODRIGUEZ; B. W. BOWEN; D. DOMNING; A. A. MIGNUCCI‐GIANNONI; M. MARMONTEL; R. A. MONTOYA‐OSPINA; B. MORALES‐VELA; M. RUDIN; R. K. BONDE; P. M. McGUIRE (Molecular Ecology, 1998)
To resolve the population genetic structure and phylogeography of the West Indian manatee ( Trichechus manatus ), mitochondrial (mt) DNA control region sequences were compared among eight locations across the western Atlantic region. Fifteen haplotypes were identified among 86 individuals from Florida, Puerto Rico, the Dominican Republic, Mexico, Colombia, Venezuela, Guyana and Brazil. Despite the manatee’s ability to move thousands of kilometres along continental margins, strong population separations between most locations were demonstrated with significant haplotype frequency shifts. These findings are consistent with tagging studies which indicate that stretches of open water and unsuitable coastal habitats constitute substantial barriers to gene flow and colonization. Low levels of genetic diversity within Florida and Brazilian samples might be explained by recent colonization into high latitudes or bottleneck effects. Three distinctive mtDNA lineages were observed in an intraspecific phylogeny of T. manatus , corresponding approximately to: (i) Florida and the West Indies; (ii) the Gulf of Mexico to the Caribbean rivers of South America; and (iii) the northeast Atlantic coast of South America. These lineages, which are not concordant with previous subspecies designations, are separated by sequence divergence estimates of d = 0.04–0.07, approximately the same level of divergence observed between T. manatus and the Amazonian manatee ( T. inunguis , n = 16). Three individuals from Guyana, identified as T. manatus , had mtDNA haplotypes which are affiliated with the endemic Amazon form T. inunguis . The three primary T. manatus lineages and the T. inunguis lineage may represent relatively deep phylogeographic partitions which have been bridged recently due to changes in habitat availability (after the Wisconsin glacial period, 10 000 BP ), natural colonization, and human‐mediated transplantation.

A comparison between laddermill and treadmill maximal oxygen consumption - M. A. Montoliu; V. Gonzalez; B. Rodriguez; L. Palenciano (European Journal of Applied Physiology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Differential effects of ventilatory stimulation by sex hormones and almitrine on hypoxic erythrocytosis - R. Favier; H. Spielvogel; E. Caceres; A. Rodriguez; B. Sempore; J. Pequignot; J. M. Pequignot (Pflügers Archiv - European Journal of Physiology, 1997)

Influence of gender and endogenous sex steroids on catecholaminergic structures involved in physiological adaptation to hypoxia - J. M. Pequignot; H. Spielvogel; E. Caceres; A. Rodriguez; B. Semporé; J. Pequignot; R. Favier (Pflügers Archiv - European Journal of Physiology, 1997)